Baseline demographic, clinical, and cognitive characteristics of the Alzheimer's Prevention Initiative (API) Autosomal‐Dominant Alzheimer's Disease Colombia Trial. Issue 7 (17th May 2020) - Rios‐Romenets, Silvia; Lopera, Francisco; Sink, Kaycee M.; Hu, Nan; Lian, Qinshu; Guthrie, Heather; Smith, Jillian; Cho, William; Mackey, Howard; Langbaum, Jessica B.; Thomas, Ronald G.; Giraldo‐Chica, Margarita; et al.
Abstract: Introduction: The API AutosomalDominant AD (ADAD) Colombia Trial is a placebo‐controlled clinical trial of crenezumab in 252 cognitively unimpaired 30 to 60‐year‐old Presenilin 1 (PSEN1) E280A kindred members, including mutation carriers randomized to active treatment or placebo and non‐carriers who receive placebo. Methods: Of the 252 enrolled, we present data on a total of 242 mutation carriers and non‐carriers matched by age range, excluding data on 10 participants to protect participant confidentiality, genetic status, and trial integrity. Results: We summarize demographic, clinical, cognitive, and behavioral data from 167 mutation carriers and 75 non‐carriers, 30 to 53 years of age. Carriers were significantly younger than non‐carriers ((mean age ± SD) 37 ± 5 vs 42 ± 6), had significantly lower Mini Mental Status Exam (MMSE) scores (28.8 ± 1.4 vs 29.2 ± 1.0), and had consistently lower memory scores. Discussion: Although PSEN1 E280A mutation carriers in the Trial are cognitively unimpaired, they have slightly lower MMSE and memory scores than non‐carriers. Their demographic characteristics are representative of the local population.